A simple route to vertical array of quasi-1D ZnO nanofilms on FTO surfaces: 1D-crystal growth of nanoseeds under ammonia-assisted hydrolysis process - Abd Rahman Mohd Yusri; Taslim Rika; Oyama Munetaka; Ali Umar Akrajas; Mat Salleh Muhamad (Nanoscale Research Letters, 2011)
Abstract A simple method for the synthesis of ZnO nanofilms composed of vertical array of quasi-1D ZnO nanostructures (quasi-NRs) on the surface was demonstrated via a 1D crystal growth of the attached nanoseeds under a rapid hydrolysis process of zinc salts in the presence of ammonia at room temperature. In a typical procedure, by simply controlling the concentration of zinc acetate and ammonia in the reaction, a high density of vertically oriented nanorod-like morphology could be successfully obtained in a relatively short growth period (approximately 4 to 5 min) and at a room-temperature process. The average diameter and the length of the nanostructures are approximately 30 and 110 nm, respectively. The as-prepared quasi-NRs products were pure ZnO phase in nature without the presence of any zinc complexes as confirmed by the XRD characterisation. Room-temperature optical absorption spectroscopy exhibits the presence of two separate excitonic characters inferring that the as-prepared ZnO quasi-NRs are high-crystallinity properties in nature. The mechanism of growth for the ZnO quasi-NRs will be proposed. Due to their simplicity, the method should become a potential alternative for a rapid and cost-effective preparation of high-quality ZnO quasi-NRs nanofilms for use in photovoltaic or photocatalytics applications. PACS: 81.07.Bc; 81.16.-c; 81.07.Gf.